Comparison of a Personalized Prostate Biopsy Pattern With Traditional Transrectal Prostate Biopsy: Different Cancer Detection Rate - Jiang, Xin; Qu, Sifeng; Zhu, Yaofeng; Wang, Shuo; Sun, Haoyu; Guo, Hu; Shi, Benkang; Chen, Shouzhen (Frontiers in Cell and Developmental Biology, 2022)
Background: In terms of prostate biopsy approaches, traditional transrectal prostate biopsy is difficult to reach the ventral central region of the prostate, while transperineal biopsy easily misses the tumor in the dorsolateral region of the prostate. However, up to date, no studies have investigated the biopsy accuracy in selective application of transrectal or transperineal biopsy according to the lesion site. Methods: We developed a personalized prostate biopsy pattern and the biopsy approach was selected individually according to the lesion site. We compared this with traditional transrectal prostate biopsy method to evaluate the efficiency. Patients (n = 351) who underwent prostate biopsy in Qilu Hospital of Shandong University from January 2018 to October 2020 were divided into two groups, including traditional transrectal prostate biopsy group (n = 236) and personalized group (n = 115). The data of this patients, including clinical characteristics, biopsy result, complications and so on was analyzed. Results: The clinical characteristics of the two groups were similar. The total detection rate of prostate cancer in the personalized group was 49.6%, which was significantly higher than 38.1% in the traditional group (P=0.037). When PSA<20ng/ml, the detection rates of the two groups were 30.4% and 19.3%, respectively (P=0.044). The PI-RADS was positively associated with high grade prostate cancer in personalized group. Patients with complications in the traditional transrectal systematic method group accounted for 6.8%, and in personalized group complications through the transrectal and transperineal approach accounted for 7.1% and 4.1%, respectively. The most common complications in transrectal group are fever and rectal bleeding, and that in transperineal group are hematuria and urinary retention. Conclusion: Compared with traditional transrectal prostate biopsy, the personalized biopsy pattern improved the detection rate of prostate cancer. The complications of transrectal approach were much higher than those in transperineal approach.